1985
DOI: 10.1128/jcm.21.3.328-331.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a latex agglutination test with five other methods for determining the presence of antibody against cytomegalovirus

Abstract: A latex agglutination test for determination of antibody against cytomegalovirus was compared with five other methods: a solid-phase fluorescent immunoassay, an indirect hemagglutination test, two solid-phase enzyme immunoassays, and an indirect fluorescent-antibody method, with sera collected from 210 random blood donors. Of the sera tested, 28% were positive for anti-cytomegalovirus by concordance of four or more methods. The latex agglutination test performed well, with a sensitivity of 100%, a specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In one of very few studies of the time course of laboratory detection of primary CMV infection in allograft recipients under immunosuppression, Pass and co-workers (19) demonstrated that serological response to infection can usually be detected before virus can be isolated. Many studies have compared CMV serological tests and commercial reagents in terms of sensitivity, specificity, and accuracy by using single serum specimens from different patients (3,16,21), but few comparisons of the abilities of different methods to detect the inception of CMV antibody production in sequential sera have been attempted. The present study was undertaken to examine patterns of antibody response by using nine serological procedures, to compare the results with those of virus isolation for the early detection of primary CMV infection in renal and heart transplant recipients, to ascertain the poten-tial diagnostic value of immunoblotting in these patients, and to identify the viral structural polypeptides involved in the very early immune response in these immunosuppressed individuals.…”
mentioning
confidence: 99%
“…In one of very few studies of the time course of laboratory detection of primary CMV infection in allograft recipients under immunosuppression, Pass and co-workers (19) demonstrated that serological response to infection can usually be detected before virus can be isolated. Many studies have compared CMV serological tests and commercial reagents in terms of sensitivity, specificity, and accuracy by using single serum specimens from different patients (3,16,21), but few comparisons of the abilities of different methods to detect the inception of CMV antibody production in sequential sera have been attempted. The present study was undertaken to examine patterns of antibody response by using nine serological procedures, to compare the results with those of virus isolation for the early detection of primary CMV infection in renal and heart transplant recipients, to ascertain the poten-tial diagnostic value of immunoblotting in these patients, and to identify the viral structural polypeptides involved in the very early immune response in these immunosuppressed individuals.…”
mentioning
confidence: 99%
“…The latex agglutination assay is simple and rapid and has been widely advocated for use in donor screening applications (1,13,18,20,25). Previous laboratory comparisons suggested high accuracy, including reports of 100% sensitivity (2,14,23). Unfortunately, we found, during 2 years of actual use of the assay in our transplant program, that occasional (about 5%) seropositive and demonstrably infective donors were missed by this assay.…”
Section: Discussionmentioning
confidence: 79%
“…It is clear from this and similar studies that no single assay provides 100% sensitivity for the determination of CMV immune status in the marrow transplant population, which includes patients as well as donors. Different assays will provide discordant results with a small number of serum samples, and consequently "true" antibody status in these patients or donors may need to be defined with additional laboratory and clinical information or both or through use of multiple serologic assays (2,(4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%